Differential migration of the sexes and other aspects of the recovery overseas of mallard ringed at Borough Fen Decoy, Northamptonshire - Ogilvie, M A; Cook, W A (Wildfowl, 1971)
Mallard Anas platyrhynchos ringed at Borough Fen Decoy, Northamptonshire, include a proportion of winter visitors of foreign origin. The sex ratio at ringing is close to 1:1 but the overseas recoveries show a marked preponderance of males in Denmark, Germany and Poland (75%) but only slightly larger numbers in France and the Low Countries or in Scandinavia and the U.S.S.R. Much larger numbers of males form the most eastern area came to Britain after 1st November in the first three years of the study (1975-58 to 1959-60) than have since. Recoveries in Britain of Mallard ringed overseas appear to confirm this finding. No such changes have occurred relating to areas closer to Britain. Abmigration may be a cause of the sexual imbalance of the recoveries. Differences between seasonal recovery patterns are examined.